Understanding the Social and Emotional Dynamics of Fatherless Adolescents Girls: A Phenomenological Studies in Turen, Malang - Sarah Dyonita; Eko Rizqi Purwo Widodo; Hutri Agustino (Jurnal Partisipatoris, 2026)
This study aims to explore and describe the social and emotional dynamics of adolescent girls in a fatherless condition study in Turen district, Malang regency. This study uses a qualitative method with a phenomenological approach, with data collection techniques in the form of in-depth interviews, observation, and documentation involving 4 adolescent girls who experience the absence of a father figure both physically and psychologically. The results of the study indicate that the absence of a father figure affects the emotional condition of adolescent girls, which is reflected in feelings of loss, loneliness, and emotional instability. From a social perspective, adolescent girls who experience the absence of a father figure experience difficulties in developing self-confidence, building interpersonal relationships, and adapting to their social environment. In facing problems, they tend to use passive coping strategies such as suppressing emotions, avoiding problems, and withdrawing from the surrounding environment, which can worsen emotional conditions if not supported by adequate social support. In conclusion, the absence of a father figure plays an important role in influencing the social and emotional conditions of adolescent girls, highlighting the importance of family and social support in promoting healthier development.